To MSNAP or not to MSNAP? Testing a small regional memory clinic against the UK Memory Service National Accreditation Program (MSNAP). (3rd May 2018) - Sweeney, E. B.; Foley, J. E.; Fitzsimons, S.; Denihan, A.
Abstract : Aim: To investigate whether a small regional memory clinic would benefit from engaging with a structured external audit process such as the Royal College of Psychiatrists' Memory Service National Accreditation Program (MSNAP). Background: The Psychiatry of Old Age service in Navan operates a public cognitive clinic. Despite the publication of the 2014 National Dementia Strategy, there are currently no national standards for memory clinics in Ireland. It may be beneficial to link in with an external quality control system as part of routine clinical governance. Methods: Published data from the MSNAP group was reviewed and a set of audit materials extrapolated to replicate the MSNAP self-review process. The audit cycle involved (1) retrospective case review, (2) institution of a range of interventions and (3) a prospective audit, which included service user feedback. Results: Overall the results demonstrated a high standard of service, especially in the areas of accessibility, assessment and communication of diagnosis. The clinic performed well against MSNAP key performance indicators. Patient and carer satisfaction with the service was very high. Clinic policies needed further development, particularly in the areas of referral, consent and data protection. Conclusions: The process was useful, providing clear pointers for action. It highlighted the need to formalise organisational and practice policies, patient support and education, audit and outreach. Although accreditation is a laborious process requiring financial investment, it provides a strong scaffold to maintain and improve standards and is likely to be a valuable learning experience, where national guidelines are lacking.